Cover, Content, and Editorial Note from Borneo J Pharm Vol. 3 No. 2 May 2020 - Chief Editor of Borneo J Pharm (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published in May 2020. Starting from this edition, Borneo J Pharm increases the frequency of publishing four times a year. This change aims to improve the circulation of the best articles published by Borneo J Pharm. Also, starting from this edition, Borneo J Pharm applying the publish-as-you-go issue to present the title of the article that has been received as early as possible in order to increase the chances of readability and quotation of articles in Borneo J Pharm. This edition contains six articles consisting of Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Microbiology Pharmacy, and Clinical-Community Pharmacy. This edition includes writings from four countries including Indonesia, India, Nigeria, and The Gambia. The authors come from several institutions, including Shri Gopichand College of Pharmacy, Universitas Halu Oleo, Universitas Airlangga, Sekolah Tinggi Ilmu Kesehatan Borneo Lestari, Universitas Muhammadiyah Bandung, Universitas Jenderal Achmad Yani, Akademi Farmasi Surabaya, Federal University Birnin-Kebbi, and London School of Hygiene and Tropical Medicine, Gambia. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for the publication in the next edition on August 2020.